THE EFFECTIVENESS OF USING TEAM ASSISTED INDIVIDUALIZATION (TAI) IN TEACHING READING COMPREHENSION - Pitoyo Yoga Pamungkas (Graduate Program, University of Islam Malang, 2021)
The purpose of this research are: (1) to find out the effectiveness of Team Assisted Individualization (TAI) to enhance a student's literal reading comprehension achievement, and (2) to find out the effectiveness of TAI to enhance students' inferential reading comprehension achievement. Pre-experimental was utilized in this research. The researcher used 32 students at IX grade of Junior High School Bustanuts Stani Jombang as the sample. This research was accomplished in five meetings as teaching, a meeting for pre-test, and a meeting for post-test. The researcher used multiple choices reading comprehension test to collect the data. The result demonstrated that the students who have been taught by TAI show a mean score of posttest comprising 59.06 which is higher than the mean score of pre-test (52.50). It indicates that the students achieve better on literal reading comprehension after being taught by applying TAI. Additionally, students who have been taught by TAI show a mean score of posttest comprising 18.75 which is higher than the mean score of the pre-test (15.16). In brief, students achieve better on inferential reading comprehension after being taught by using TAI.Keywords: Team Assisted Individualization (TAI), Reading Comprehension